Persepsi Mahasiswa Program Studi Gizi Terhadap Program Merdeka Belajar-Kampus Merdeka di Lingkungan Universitas Al-Azhar Indonesia - Amalina Ratih Puspa; Elma Alfiah (Universitas Al Azhar Indonesia, 2022)
Kebijakan Merdeka Belajar-Kampus Merdeka (MBKM) is the Right to Study for Three Semesters Outside the Study Program. The MBKM policy is expected to be able to answer challenges and opportunities for the development of innovation, creativity, capacity, personality, and student needs, as well as develop independence in seeking and finding knowledge through realities and field dynamics. The purpose of this population survey is to determine the impact of MBKM in the Nutrition Study Program, Faculty of Science and Technology, Al Azhar University Indonesia, and provide policy recommendations from the study program level related to the implementation of MBKM at Al Azhar University Indonesia. The perception of most students of the Nutrition Studies Program, Faculty of Science and Technology, University of Al Azhar Indonesia towards the MBKM was the program is important, and it can provide additional competencies (problem-solving, problem analysis, and work ethics) and train students' soft skills. However, on the other hand, there are obstacles to its implementation, considering that the Nutrition Study Program is one of the Health Study Programs. In addition, the socialization of the MBKM program related to health study programs is still minimal so the Nutrition Study Program has not been able to fully implement and feel the benefits. It is necessary to have a university policy that accommodates the MBKM program for health study programs.Keywords - Benefit, MBKM, Nutrition Study Program, Recommendation, Universitas Al Azhar Indonesia